ANALISIS BENTUK PARTISIPASI POLITIK MAHASISWA PERANTAUAN KECAMATAN GUNUNG RAYA PADA PILKADA KABUPATEN KERINCI TAHUN 2024 - Beti Zania; Tohap Pandapotan Simaremare; Dona Sariani (Jurnal Pancasila dan Kewarganegaraan (JUPANK), 2025)
This study aims to determine the form of political participation of migrant students from Gunung Raya District in the 2024 Kerinci Regency Regional Head Election (Pilkada). Students as young voters have a strategic role in democracy. The background of this study is the low level of attendance and active political participation of migrant students in the Pilkada, even though they are a potential young voter group. This study uses a qualitative descriptive case study approach with data collection through interviews, observations, and documentation. The results of the study show that the forms of student political participation include: voting, many cannot attend the Polling Station which is hampered by costs and distance, including potential contributors to abstaining from voting in Gunung Raya District. Campaign activities are carried out more online than in person. Communal activities with minimal involvement; political communication is limited to personal circles. and low participation in Protest actions due to concerns and lack of understanding of issues. Students have great potential to be involved in politics, but their participation is still limited to certain forms.